Profile Of Homicidal Deaths: A Three-Year Study at Surat Municipal Institute of Medical Education and Research, Surat During 2011 -13 - Shailesh Jhaveri; Sandip Raloti; Rajesh Patel; Jignesh Brahbhatt; Vijay Kaushik (Medsci Publications, 2014)
Background: This study is done to know different aspects of homicidal deaths such as age and sex of the victim, incidence in various areas, seasonal variation, survival time, types of injuries, body part involved, organs involved, modes of death, homicidal deaths presented as accidental one by investigating officer and post - mortem burns after homicide in Surat city and to compare these aspects with other studies. Methods: This retrospective study is carried out by analysis of data from post - mortem reports, inquest papers and post mortem registers of the Forensic Medicine and Toxicology Department of SMIMER. The analysis of the data is done manually by calculator and excels spreadsheet of window 8. Results: Among 4524 autopsies conducted during 2011 -2013, homicidal deaths were 106, i.e. 2.34%.Bulk of the victims was males, i.e.86.69% while females comprise only 13.21%. Stab wounds and blunt injuries were major injuries responsible for deaths, constitute 41.51% and 40.55% respectively. Multiple regions of the body were involved in 43.4% while brain was the commonest organ to get injured (26.42%) followed by lungs (10.38) and heart (8.49%). Conclusion: There is slight decreasing trend of homicidal deaths. The incidence has also reduced to less than half over a period of two decades in the city. Asphyxial deaths constitute one out of five homicidal deaths.